Light guide plate for displaying image
Patent Information
- Application Number
- JP2024214405
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-26
AI Technical Summary
【0009】 本発明によれば、ホログラム層の劣化を抑制でき、かつ、良好な光学特性を有する画像表示用導光板を提供できる。
Smart Images

Figure 2025041685000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a light guide plate for image display. [Background technology]
[0002] In some display devices, a light guide plate for image display is used. For example, in a display device using VR (Virtual Reality) technology or AR (Augmented Reality) technology, a light guide plate for image display in which a hologram layer is supported on a transparent substrate is used. In the hologram layer, a hologram having various optical functions, such as wave guidance, reflection, and diffraction, is formed. The materials used for forming the hologram layer are often photosensitive compositions containing radical polymerizable monomers, polyacids, or bases such as amines, which may deteriorate the resin substrate. It is also known that the hologram material deteriorates due to moisture absorption. For this reason, a display device in which the hologram layer is supported by a resin substrate is easily deteriorated in a high-temperature and high-humidity environment.
[0003] Patent Document 1 describes forming a photosensitive material layer for forming a hologram on an optically transparent resin substrate, and covering the photosensitive material layer with an aqueous polymer protective barrier. Patent Document 1 suggests that the aqueous polymer protective barrier is provided for the purpose of resisting attack by moisture. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 5-181400 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the technique described in Patent Document 1 has the following problems. In the technique described in Patent Document 1, a resin substrate is adhered to the surface of the photosensitive material layer opposite the aqueous polymer protective barrier. Therefore, the photosensitive material may corrode the resin base in a high-temperature environment. Furthermore, since moisture is contained inside the resin base, the moisture diffuses into the photosensitive material layer through the contact surface with the photosensitive material layer. In addition, since the base is exposed to the outside, moisture continues to permeate the base from the outside. As a result, since moisture permeates the photosensitive material layer via the resin base, even if the moisture is blocked by the aqueous polymer protective barrier, it is not possible to prevent the photosensitive material layer from deteriorating over time due to moisture from the base side.
[0006] An object of the present invention is to provide a light guide plate for image display that can suppress deterioration of a hologram layer and has good optical characteristics. [Means for solving the problem]
[0007] The present inventors have discovered that by providing an anchor coat layer and a barrier layer made of a specific material between a resin substrate and a hologram layer, deterioration of the hologram layer can be suppressed and good optical properties can be obtained in a light guide plate for image display, and have completed the present invention. That is, the present invention has the following aspects.
[0008] [1] A light guide plate for image display, comprising: a first laminate having a first resin substrate, a first anchor coat layer, and a first barrier layer in this order; and a hologram layer, wherein the first barrier layer is mainly composed of silicon oxynitride, and the nitrogen element composition in the first barrier layer, as determined by X-ray photoelectron spectroscopy (XPS), is more than 0 atm% and 25 atm% or less. [2] The light guide plate for image display according to [1], wherein the first resin substrate contains at least one resin selected from the group consisting of poly(meth)acrylic resins, epoxy resins, cyclic polyolefin resins, and polycarbonate resins. [3] The light guide plate for image display according to [1] or [2], wherein the first anchor coat layer contains at least one resin selected from the group consisting of acrylic resins, urethane resins, and polyester resins. [4] The light guide plate for image display according to any one of [1] to [3], wherein the first laminate has a first hard coat layer on both surfaces of the first resin substrate. [5] The light guide plate for image display according to any one of [1] to [4], wherein the first laminate has a total light transmittance of 90% or more. [6] The light guide plate for image display according to any one of [1] to [5], wherein the haze of the first laminate is less than 0.1%. [7] The light guide plate for image display according to any one of [1] to [6], wherein b* of the first laminate measured by a spectrophotometer is less than 0.5. [8] The water vapor permeability of the first laminate is 0.01 g / m 2 / day or less. The light guide plate for image display according to any one of [1] to [7]. Effect of the Invention
[0009] According to the present invention, it is possible to provide a light guide plate for image display that can suppress deterioration of a hologram layer and has good optical characteristics. [Brief description of the drawings]
[0010] [Figure 1] 1 is a schematic cross-sectional view showing an example of a light guide plate for image display of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention will be described. However, the present invention is not limited to the embodiment described below, and various modifications are possible without departing from the gist of the present invention. In the present invention, "(meth)acrylic" includes "acrylic" and "methacrylic." For example, "poly(meth)acrylic resin" includes "polyacrylic resin" and "polymethacrylic resin."
[0012] <Light guide plate for image display> A light guide plate for image display according to an embodiment of the present invention will be described. The light guide plate for image display of this embodiment has a first laminate including a first resin substrate, a first anchor coat layer, and a first barrier layer, and a hologram layer. The first resin substrate, the first anchor coat layer, the first barrier layer, and the hologram layer are arranged in this order in the thickness direction. The first laminate may be arranged on at least one surface of the hologram layer, but may be arranged on both surfaces of the hologram layer. When the first laminate is arranged on both surfaces of the hologram layer, the first laminate arranged on one surface of the hologram layer is called the first laminate, and the first laminate arranged on the other surface of the hologram layer is called the second laminate. In this case, the hologram layer is sandwiched between the first barrier layer of the first laminate and the second barrier layer of the second laminate, the first anchor coat layer and the first resin substrate are laminated on the other surface of the first barrier layer, and the second anchor coat layer and the second resin substrate are laminated on the other surface of the second barrier layer. In this embodiment, the first laminate and the second laminate may be collectively referred to simply as "laminate" below. The first resin substrate and the second resin substrate may hereinafter be collectively referred to simply as "resin substrate". The first anchor coat layer and the second anchor coat layer may hereinafter be collectively referred to simply as "anchor coat layer". Furthermore, the first barrier layer and the second barrier layer may hereinafter be collectively referred to simply as "barrier layer".
[0013] One or more transparent layers may be disposed between the first resin substrate and the first anchor coat layer, between the first anchor coat layer and the first barrier layer, and between the first barrier layer and the hologram layer. Examples of the transparent layer include a hard coat layer.
[0014] The light guide plate for image display has an incident portion for receiving image light and a display portion for displaying an image based on the image light. The hologram layer is disposed between the incident portion and the display portion, and has a diffraction grating pattern formed on the hologram layer for guiding at least the image light incident from the incident portion to the display portion and for causing the image light to exit from the display portion. The diffraction grating pattern in the display portion transmits at least a part of external light incident from outside the image display light guide plate, the external light being incident from the surface opposite to the display portion.
[0015] The image light incident on the incident portion is guided into the hologram layer and is emitted to the outside from the display portion. Meanwhile, external light also passes through the resin base material and the display portion, so that a viewer of the display portion can view both the image light and the external light within his or her field of view. The light guide plate for image display of this embodiment can be used in display devices using VR (virtual reality) technology or AR (augmented reality) technology, and can be used, for example, in in-vehicle displays or sports sunglasses for outdoor use. Furthermore, the light guide plate for image display of this embodiment can be used not only for display applications, but also for devices such as a combiner for a head-up display (HUD) mounted on an automobile or a holographic optical element (HOE) represented by a reflector for a reflective liquid crystal display device.
[0016] Hereinafter, a detailed configuration of an example of the light guide plate for image display of this embodiment will be described based on the example shown in Fig. 1. Fig. 1 is a schematic cross-sectional view showing an example of the light guide plate for image display of the embodiment of the present invention.
[0017] In the light guide plate 8 for image display shown in Figure 1, a first resin base material 1, a first anchor coat layer 2, a first barrier layer 3, a hologram layer 4, a second barrier layer 5, a second anchor coat layer 6 and a second resin base material 7 are arranged in this order in the thickness direction. There is no particular limitation on the planar shape of the image display light guide plate 8. For example, the image display light guide plate 8 may be shaped so as to be attachable to a display device in which it is used. For example, the light guide plate 8 for image display may be a rectangular plate larger than the shape to be attached to the display device. In this case, the light guide plate 8 for image display is cut or otherwise shaped into a shape that can be attached to the display device before being assembled into the display device. The image display light guide plate 8 may be in the form of a flat plate, or may be in the form of a curved plate as required. In the following, an example will be described in which the image display light guide plate 8 is made of a flat plate that is rectangular in plan view.
[0018] [First laminate] The first laminate includes, in this order, a first resin substrate 1, a first anchor coat layer 2, and a first barrier layer 3. By disposing the first laminate on the surface of the hologram layer 4, the image display light guide plate 8 can suppress deterioration of the hologram layer and obtain good optical properties.
[0019] (Optical properties) The total light transmittance of the first laminate is not particularly limited, but is preferably 90% or more, more preferably 91% or more, and even more preferably 92% or more. When the total light transmittance of the first laminate is 90% or more, the luminance value of the light guide plate for image display 8 becomes better. From the same viewpoint, the haze of the first laminate is preferably less than 0.1%, more preferably less than 0.08%, even more preferably less than 0.06%, and even more preferably less than 0.05%.
[0020] The absolute value of b* of the first laminate measured by a spectrophotometer is preferably less than 0.8, more preferably less than 0.6, and even more preferably less than 0.5. Among these, it is more preferably less than 0.4, even more preferably less than 0.3, and even more preferably less than 0.1. When the absolute value of b* of the first laminate is less than 0.8, the luminance value and clarity of the light guide plate 8 for image display become better.
[0021] (Barrier properties) The water vapor permeability of the first laminate is 0.01 g / m 2 / day is preferable, and 0.008 g / m 2 / day is more preferable, and 0.006 g / m2 / day is more preferable, and 0.004 g / m 2 / day is even more preferable. The water vapor transmission rate of the first laminate is 0.01 g / m 2 When the exposure time is less than 10 minutes / day, the deterioration of the hologram layer 4 can be further suppressed.
[0022] [First resin base material 1] The first resin base material 1 is disposed at the outermost part in the thickness direction of the light guide plate for image display 8. The first resin base material 1 is disposed on the surface of the light guide plate for image display 8 on the display image output side. The first resin base material 1 has the same external shape as the light guide plate 8 for image display. The first resin base material 1 transmits image light emitted from the hologram layer 4 and external light that transmits through the second resin base material 7 and the hologram layer 4, which will be described later.
[0023] The thickness of the first resin base material 1 is not particularly limited, but is preferably 0.05 to 10 mm. There is no particular lower limit to the thickness of the first resin base material 1, but from the viewpoint of improving scratch resistance, it is preferably 0.1 mm or more, and more preferably 0.2 mm or more. The upper limit of the thickness of the first resin base material 1 is not particularly limited, but from the viewpoint of improving moldability and total light transmittance, it is preferably 5 mm or less, more preferably 3 mm or less, and even more preferably 2 mm or less. In this specification, the thickness of the first resin base material 1 can be measured by a dial gauge using a stylus, a micrometer, or the like.
[0024] The total light transmittance of the first resin base material 1 is not particularly limited, but is preferably 80% or more, and more preferably 90% or more. When the total light transmittance of the first resin base material 1 is 80% or more, the luminance value of the light guide plate for image display 8 becomes better.
[0025] The first resin base material 1 preferably contains a thermoplastic resin from the viewpoint of improving optical properties, impact resistance, scratch resistance, and moldability. Examples of the thermoplastic resin include polyolefin-based resins such as homopolymers or copolymers of alkenes such as ethylene, propylene, and butene; amorphous polyolefin-based resins such as cyclic polyolefin-based resins; polyester-based resins such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN); cellulose-based resins such as triacetyl cellulose, diacetyl cellulose, and cellophane; polyamide-based resins such as nylon 6, nylon 66, nylon 12, and copolymer nylon; ethylene-vinyl acetate copolymer partial hydrolyzate (EVOH); polyimide-based resins; polyetherimide-based resins; polysulfone-based resins; Examples of the thermoplastic resin include polyethersulfone resin, polyetheretherketone resin, polycarbonate resin, polyvinylbutyral resin, polyarylate resin, fluorine resin, poly(meth)acrylic resin, styrene resin such as polystyrene, polyvinyl alcohol, ethylene vinyl alcohol copolymer, polyvinyl chloride, cellulose, acetyl cellulose, polyvinylidene chloride, polyphenylene sulfide, polyurethane, phenol resin, epoxy resin, polynorbornene, styrene-isobutylene-styrene block copolymer (SIBS), allyl diglycol carbonate, and organic materials such as biodegradable resin. These thermoplastic resins can be used alone or in combination of two or more. The first resin substrate 1 may also be configured by laminating layers made of two or more materials selected from the group consisting of the above thermoplastic resins. In the present invention, from the viewpoint of transparency, at least one resin selected from the group consisting of poly(meth)acrylic resins, epoxy resins, cyclic polyolefin resins, and polycarbonate resins is preferred. Among these, poly(meth)acrylic resins are preferred because of their excellent scratch resistance and moldability.
[0026] (Poly(meth)acrylic resin) Examples of monomers constituting the poly(meth)acrylic resin include methyl methacrylate, methacrylic acid, acrylic acid, benzyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, glycidyl (meth)acrylate, hydroxypropyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, norbornyl (meth)acrylate, Examples of the monomer include dicyclopentenyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, acrylic (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl maleate, 2-(meth)acryloyloxyethyl phthalate, 2-(meth)acryloyloxyethyl hexahydrophthalate, pentamethylpiperidyl (meth)acrylate, tetramethylpiperidyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and diethylaminoethyl (meth)acrylate. These monomers may be used by polymerizing alone or by polymerizing two or more kinds.
[0027] In addition, other monomers copolymerizable with the monomers constituting the poly(meth)acrylic resin may be added. The other monomers may be monofunctional monomers, i.e., compounds having one polymerizable carbon-carbon double bond in the molecule, or polyfunctional monomers, i.e., compounds having at least two polymerizable carbon-carbon double bonds in the molecule. Examples of the monofunctional monomer include aromatic alkenyl compounds such as styrene, α-methylstyrene, and vinyltoluene, alkenyl cyanide compounds such as acrylonitrile and methacrylonitrile, acrylic acid, methacrylic acid, maleic anhydride, and N-substituted maleimides. Examples of the polyfunctional monomer include polyunsaturated carboxylic acid esters of polyhydric alcohols such as ethylene glycol dimethacrylate, butanediol dimethacrylate, and trimethylolpropane triacrylate; alkenyl esters of unsaturated carboxylic acids such as allyl acrylate, allyl methacrylate, and allyl cinnamate; polyalkenyl esters of polybasic acids such as diallyl phthalate, diallyl maleate, triallyl cyanurate, and triallyl isocyanurate; and aromatic polyalkenyl compounds such as divinylbenzene. The monofunctional monomers and polyfunctional monomers can be used alone or in combination of two or more.
[0028] The poly(meth)acrylic resin can be produced by polymerizing the above-mentioned monomer components by a known method such as suspension polymerization, emulsion polymerization, or bulk polymerization.
[0029] [First anchor coat layer 2] The first anchor coat layer 2 is disposed between the first resin substrate 1 and the first barrier layer 3. By providing the first anchor coat layer 2, the adhesion between the first resin substrate 1 and the first barrier layer 3 is improved, and the barrier property is improved.
[0030] The first anchor coat layer 2 also plays a role in alleviating residual stress that occurs when the first barrier layer 3 described below is formed by dry film formation. Furthermore, it can also suppress deformation of the first barrier layer 3 in a humid and hot environment (e.g., 40°C, 90% RH), and prevent an increase in haze of the light guide plate 8 for image display. From the viewpoint of sufficiently relaxing the residual stress of the first barrier layer 3, the thickness of the first anchor coat layer 2 is preferably 1 nm or more, more preferably 3 nm or more, and even more preferably 5 nm or more. On the other hand, from the viewpoint of preventing the first barrier layer 3 from being too greatly deformed by the residual stress, the thickness of the first anchor coat layer 2 is preferably 200 nm or less, more preferably 150 nm or less, and even more preferably 100 nm or less. Furthermore, from the viewpoint of sufficiently relaxing the residual stress in the first barrier layer 3 and preventing the first barrier layer 3 from being too significantly deformed due to the residual stress, the thickness of the first anchor coat layer 2 is preferably 1 to 200 nm, more preferably 3 to 150 nm, and even more preferably 5 to 100 nm.
[0031] When the first resin substrate 1 is made of a resin having high moisture absorption properties such as a poly(meth)acrylic resin, the first resin substrate 1 may expand in a humid and hot environment. From the viewpoint of being able to follow the expansion of the first resin substrate 1 in a humid and hot environment, the tan δ peak temperature in the viscoelasticity measurement of the first anchor coat layer 2 is preferably 80° C. or lower, and more preferably 75° C. or lower. On the other hand, from the viewpoint of preventing the first anchor coat layer 2 from being too deformed due to the residual stress of the first barrier layer 3, the tan δ peak temperature in the viscoelasticity measurement of the first anchor coat layer 2 is preferably 10° C. or higher, more preferably 15° C. or higher, and even more preferably 20° C. or higher. Furthermore, from the viewpoint of enabling the first anchor coat layer 2 to follow the expansion of the first resin substrate 1 in a humid and hot environment and preventing the first anchor coat layer 2 from being too greatly deformed due to the residual stress of the first barrier layer 3, the tan δ peak temperature in the viscoelasticity measurement of the first anchor coat layer 2 is preferably 10 to 80°C, more preferably 15 to 80°C, and even more preferably 20 to 75°C. In this specification, the tan δ peak temperature is the peak temperature of the loss tangent (tan δ) when a sheet having a thickness of 200 μm is prepared from the first anchor coat layer 2 and viscoelasticity measurements are performed using a dynamic viscoelasticity measuring device (DVA-200, manufactured by IT Measurement and Control Co., Ltd.) under conditions of a frequency of 1 Hz, a heating rate of 3°C / min, and a measurement temperature of -50 to 200°C.
[0032] The total light transmittance of the first anchor coat layer 2 is not particularly limited, but is preferably 80% or more, and more preferably 90% or more. When the total light transmittance of the first anchor coat layer 2 is 80% or more, the luminance value of the light guide plate for image display 8 becomes good.
[0033] Furthermore, when the average refractive index of the first resin substrate 1 and the first barrier layer 3 is n1, the refractive index n2 of the first anchor coat layer 2 is preferably within the range of n1±0.20, more preferably within the range of n1±0.15, and even more preferably within the range of n1±0.10. When the refractive index n2 of the first anchor coat layer 2 is within the range of n1±0.20, the luminance value of the light guide plate for image display 8 becomes good and color unevenness can be prevented. The refractive index was measured using an Abbe refractometer (NAR-4T, manufactured by Atago Co., Ltd.).
[0034] The material of the first anchor coat layer 2 is not particularly limited, but examples thereof include a thermoplastic resin or a curable resin. Examples of the thermoplastic resin include fluorine-based resins, polyethersulfone-based resins, polycarbonate-based resins, acrylic-based resins, silicone-based resins, cycloolefin-based resins, thermoplastic polyimide-based resins, polyamide-based resins, polyamideimide-based resins, polyarylate-based resins, polysulfone-based resins, polyetherimide-based resins, polyetheretherketone-based resins, polyethersilicon-based resins, polyester-based resins, and polyphenylene sulfide-based resins. Examples of the curable resin include acrylic resins, urethane resins, epoxy resins, and silicone resins. Among these, from the viewpoint of water vapor barrier properties, acrylic resins or polyester resins are preferred as thermoplastic resins.
[0035] A silane coupling agent, a sensitizer, a crosslinking agent, an ultraviolet absorber, a polymerization inhibitor, a surfactant, a filler, a release agent, and a thermoplastic resin other than the above may be added to the resin composition constituting the first anchor coat layer 2. These additives may be used alone or in combination of two or more. In particular, the first anchor coat layer 2 preferably contains a crosslinking agent. Examples of the crosslinking agent include an isocyanate-based crosslinking agent, a peroxide-based crosslinking agent, an epoxy-based crosslinking agent, and an imine-based crosslinking agent, and an isocyanate-based crosslinking agent is preferred. The content of the crosslinking agent is preferably 0 to 20 parts by mass, more preferably 5 to 15 parts by mass, relative to 100 parts by mass of the thermoplastic resin or the curable resin.
[0036] The first anchor coat layer 2 can be formed, for example, by applying a resin composition for forming the first anchor coat layer 2 to the first resin substrate 1, laminating the first barrier layer 3 thereon, and treating this laminate with a method such as pressing, nip rolling, or heat lamination. When the first anchor coat layer 2 is made of a curable resin, the formation of the first anchor coat layer 2 may include a curing step.
[0037] [First barrier layer 3] The first barrier layer 3 is disposed between the first anchor coat layer 2 and a hologram layer 4 which will be described later. The first barrier layer 3 prevents gases such as water vapor and oxygen, which permeate from the outside of the light guide plate for image display 8 and from the first resin base material 1, from permeating into the hologram layer 4 and causing deterioration. Therefore, the smaller the oxygen permeability and water vapor permeability of the first barrier layer 3, the more preferable. The oxygen permeability of the first barrier layer 3 is 1 cm 3 / m 2 The water vapor transmission rate of the first barrier layer 3 is preferably 1 g / m 2 / day or less is preferable, and 0.5g / m 2 / day or less is more preferable, and 0.1g / m 2 / day or less is more preferable. Here, the oxygen permeability is the oxygen permeability measured using an oxygen permeability measuring device (OX-TRAN 2 / 21, manufactured by MOCON). Also, the water vapor permeability is the water vapor permeability measured using a water vapor permeability measuring device (DELTAPERM, manufactured by Technolox).
[0038] The first barrier layer 3 contains silicon oxynitride as a main component. Here, "the main component of the first barrier layer 3" refers to a component that accounts for 50 mass% or more of all components constituting the first barrier layer 3. The proportion of silicon oxynitride in the first barrier layer 3 is not particularly limited as long as it is 50 mass% or more relative to the total mass of the first barrier layer, but is preferably 60 mass% or more, more preferably 70 mass% or more, and even more preferably 80 mass% or more.
[0039] The nitrogen element composition in the first barrier layer 3 determined by X-ray Photoelectron Spectroscopy (XPS) is more than 0 atm% and not more than 25 atm%, preferably from 2 atm% to 23 atm%, more preferably from 5 atm% to 20 atm%, and even more preferably from 10 atm% to 17 atm%. When the nitrogen element composition is within the above range, the transparency of the first barrier layer 3 is increased, and the optical properties of the light guide plate 8 for image display are improved.
[0040] When the first barrier layer 3 is formed by dry film formation, residual stress may be generated that causes the first barrier layer 3 to curl outward. From the viewpoint of preventing this residual stress from becoming too large, the thickness of the first barrier layer 3 is preferably 150 nm or less, and more preferably 130 nm or less. On the other hand, from the viewpoint of improving the barrier property, the thickness of the first barrier layer 3 is preferably 5 nm or more, and more preferably 10 nm or more.
[0041] From the viewpoint of preventing deformation due to residual stress in the first barrier layer 3, the total thickness of the first anchor coat layer 2 and the first barrier layer 3 is preferably 300 nm or less, more preferably 250 nm or less, and even more preferably 200 nm or less. On the other hand, from the viewpoint of sufficiently alleviating the above-mentioned residual stress by the first anchor coat layer 2 and also improving the barrier properties of the first barrier layer 3, the total thickness of the first anchor coat layer 2 and the first barrier layer 3 is preferably 30 nm or more, and more preferably 50 nm or more.
[0042] The first barrier layer 3 preferably has a higher refractive index than the first resin base material 1. For example, when an acrylic resin is used as the first resin base material 1, the refractive index of the first barrier layer 3 is preferably 1.48 or more, more preferably 1.48 to 3.0. If the first barrier layer 3 has a higher refractive index than the first resin base material 1, the light passing through the first resin base material 1 via the first barrier layer 3 will enter the optically coarse first resin base material 1 from the optically dense first barrier layer 3, and the exit angle of the light from the first barrier layer 3 toward the first resin base material 1 will be larger according to the difference in refractive index between the first barrier layer 3 and the first resin base material 1. This makes it possible to widen the FOV (Field of View) of the present light guide plate for image display.
[0043] The first barrier layer 3 can be formed by a conventionally known film formation method such as a vacuum deposition method, a sputtering method, an ion plating method, a plasma CVD method, etc. Among them, the sputtering method is preferable as the film formation method from the viewpoint of obtaining good barrier properties and improving the clarity of the light guide plate 8 for image display. In order to improve the adhesion between the first anchor coat layer 2 and the first barrier layer 3, the surface of the first anchor coat layer 2 may be subjected to a surface treatment such as corona discharge treatment or low-temperature plasma treatment, coating with a silane coupling agent, or coating with a mixture of saturated polyester and isocyanate. When the first barrier layer 3 is formed by, for example, a vacuum deposition method, silicon, silicon monoxide, silicon dioxide, silicon oxynitride, or a mixture thereof is used as an evaporation material, and the evaporation material is 1.0×10 -3 ~2.0×10 -1 Under a vacuum of 10 Pa, the material is heated and evaporated using an electron beam, resistance heating, or high-frequency heating method. As a film formation method, for example, a reactive vapor deposition method in which oxygen gas or nitrogen gas is supplied can also be used. In addition, when forming a film by a sputtering method, for example, silicon, silicon monoxide, silicon dioxide, silicon oxynitride, or a mixture thereof is used as a target, and the concentration of the target is 1.0×10 -2 ~5.0×10 -1 The film can be formed under a vacuum of 10 Pa. As the sputtering method, for example, a reactive sputtering method in which oxygen gas, nitrogen gas or argon gas is supplied can also be used.
[0044] The nitrogen element composition in the first barrier layer 3 can be adjusted by the nitrogen flow rate, power and deposition pressure during deposition. In particular, to set the nitrogen element composition to more than 0 atm% and 25 atm% or less, the ratio O2 / N2 of the oxygen flow rate O2 [sccm] to the nitrogen flow rate N2 [sccm] is preferably 0.10 to 1.5, more preferably 0.12 to 1.0, and even more preferably 0.15 or more. Moreover, the power is preferably 1000 to 2000 W. Since O2 / N2 and power have a mutual effect, when O2 / N2 is 0.10 or more and less than 0.15, the power is preferably 1000 W or more and less than 1500 W, and when O2 / N2 is 0.15 or more and 1.5 or less, the power is preferably 1500 W or more and 2000 W or less. The deposition pressure was 1.0×10 -2 ~2.0×10 -1 Pa is preferred, 5.0×10 -2 ~1.5×10 -1 Pa is preferred.
[0045] The silicon oxynitride forming the first barrier layer 3 may contain calcium, magnesium, or oxides thereof as impurities in an amount of 10 mass % or less.
[0046] The first barrier layer 3 may contain an inorganic material other than the silicon oxynitride, such as silicon oxide, diamond-like carbon (DLC), and aluminum oxide.
[0047] [Holographic layer 4] The hologram layer 4 is disposed on the surface of the first barrier layer 3 opposite to the surface to which the first anchor coat layer 2 is adhered. In the hologram layer 4, a diffraction grating corresponding to the function to be provided by the light guide plate 8 for image display is appropriately formed.
[0048] The material of the hologram layer 4 is not particularly limited, and any known resin material for forming a hologram can be used. Examples of materials for the hologram layer 4 include a hologram recording material containing a thermosetting resin having at least one solvent-soluble, cationic polymerizable ethylene oxide ring in its structural unit, and a radically polymerizable ethylenic monomer (see JP-A-9-62169, JP-A-11-161141, and JP-A-2002-310932). Specifically, the hologram layer 4 is preferably formed from a photosensitive material containing an epoxy resin such as a bisphenol-based epoxy resin, a (meth)acrylate such as triethylene glycol diacrylate, a photopolymerization initiator such as 4,4'-bis(tert-butylphenyl)iodonium hexafluorophosphate, a wavelength sensitizer such as 3,3'-carbonylbis(7-diethylamino)coumarin, and an organic solvent such as 2-butanone.
[0049] [Second laminate] The second laminate includes, in this order, a second barrier layer 5, a second anchor coat layer 6, and a second resin substrate 7. Various physical properties of the second laminate may be different from those of the first laminate.
[0050] [Second barrier layer 5] The second barrier layer 5 is laminated on the opposite side of the first barrier layer 3 with the hologram layer 4 interposed therebetween. The second barrier layer 5 has a structure similar to that exemplified in the description of the first barrier layer 3. However, the thickness, material, etc. of the second barrier layer 5 may be different from those of the first barrier layer 3.
[0051] [Second anchor coat layer 6] The second anchor coat layer 6 is disposed between the second barrier layer 5 and the second resin substrate 7. The second anchor coat layer 6 has a configuration similar to that exemplified in the description of the first anchor coat layer 2. However, the thickness, material, etc. of the second anchor coat layer 6 may be different from those of the first anchor coat layer 2.
[0052] [Second resin base material 7] The second resin base material 7 is laminated on the surface of the second barrier layer 5. The second resin base material 7 has a structure similar to that exemplified in the description of the first resin base material 1. However, the thickness, material, and the like of the second resin base material 7 may be different from those of the first resin base material 1. In particular, since the second resin base material 7 is disposed on the surface on the external light incident side, which is located opposite to the display image exit side of the light guide plate 8 for image display, a material having a higher surface hardness than the first resin base material 1 may be used.
[0053] [Light guide plate for image display 8] In the light guide plate 8 for image display, a first anchor coat layer 2 and a first barrier layer 3, and a second barrier layer 5 and a second anchor coat layer 6 are arranged between a first resin substrate 1 and a hologram layer 4, and between a second resin substrate 7 and a hologram layer 4, respectively. Gas outside the light guide plate 8 for image display permeates the first resin base material 1 and the second resin base material 7 to a certain extent and accumulates inside. At this time, moisture in particular is likely to accumulate in the first resin base material 1 and the second resin base material 7. However, according to the configuration of this embodiment, moisture that has permeated into the first resin base material 1 and the second resin base material 7 from the outside can be blocked by the first barrier layer 3 and the second barrier layer 5, so that the permeation of water vapor into the hologram layer 4 is suppressed, and deterioration of the hologram layer 4 can be prevented.
[0054] The chemical resistance of the first resin base material 1 and the second resin base material 7 is far lower than that of glass, although the degree of resistance varies depending on the type of resin material, and therefore the first resin base material 1 and the second resin base material 7 have lower solvent resistance and hologram material resistance than glass. When the first resin base material 1 and the second resin base material 7 are in contact with the hologram layer 4, the hologram agent, which is a component of the hologram layer 4, is likely to pass through the first resin base material 1 and the second resin base material 7, and the hologram agent is likely to accumulate inside the first resin base material 1 and the second resin base material 7. When the first resin base material 1 and the second resin base material 7 are exposed to the hologram agent, the first resin base material 1 and the second resin base material 7 are deteriorated, and a decrease in FOV (Field of View) and a decrease in clarity are likely to occur. However, according to the configuration of this embodiment, the first barrier layer 3 and the second barrier layer 5 are provided between the first resin base material 1 and the hologram layer 4 and between the second resin base material 7 and the hologram layer 4, respectively, thereby suppressing the penetration of the hologram agent into the first resin base material 1 and the second resin base material 7, and thereby preventing deterioration of the first resin base material 1.
[0055] [Hard coat layer] The light guide plate for image display of this embodiment may have a hard coat layer on one or both surfaces of the first resin substrate for the purpose of increasing the pencil hardness of the surface of the first resin substrate or for the purpose of reducing the surface roughness Sa of the first barrier layer.
[0056] The hard coat layer is preferably formed from a curable resin composition. The curable resin composition is not particularly limited, but is preferably one that is cured by irradiation with energy rays such as electron beams, radiation, or ultraviolet rays, or one that is cured by heating, and is more preferably an ultraviolet-curable resin composition from the viewpoint of molding time and productivity.
[0057] Examples of the curable resin constituting the curable resin composition include acrylate compounds, urethane acrylate compounds, epoxy acrylate compounds, carboxyl group-modified epoxy acrylate compounds, polyester acrylate compounds, copolymer acrylates, alicyclic epoxy resins, glycidyl ether epoxy resins, vinyl ether compounds, and oxetane compounds. The curable resins may be used alone or in combination of two or more. Among these curable resins, radical polymerization type curable compounds such as polyfunctional acrylate compounds, polyfunctional urethane acrylate compounds, and polyfunctional epoxy acrylate compounds, and thermal polymerization type curable compounds such as alkoxysilanes and alkylalkoxysilanes are preferred because they can impart excellent surface hardness to the hard coat layer.
[0058] The curable resin composition forming the hard coat layer may contain a leveling agent as a surface adjusting component. Examples of the leveling agent include a fluorine-based leveling agent, a silicone-based leveling agent, and an acrylic-based leveling agent. Among these leveling agents, an acrylic-based leveling agent is preferred because it can ensure excellent adhesion when the first barrier layer is laminated on the surface of the hard coat layer.
[0059] When the curable resin composition is cured by ultraviolet light, a photopolymerization initiator is used. Examples of the photopolymerization initiator include benzil, benzophenone and its derivatives, thioxanthones, benzil dimethyl ketals, α-hydroxyalkylphenones, hydroxyketones, aminoalkylphenones, and acylphosphine oxides. The amount of the photopolymerization initiator added is usually 0.1 to 8 parts by mass with respect to 100 parts by mass of the curable resin composition.
[0060] The curable resin composition forming the hard coat layer may contain a refractive index adjusting component. Examples of the refractive index adjusting component include fine particles of a refractive index adjusting component, such as fine particles of a high refractive index metal compound such as zinc oxide, zirconium oxide, or titanium oxide, or fine particles of a low refractive index metal compound such as magnesium fluoride. Here, it is preferable that the size of the fine particles of the refractive index adjusting component is 5 to 50 nm, since the transparency and total light transmittance of the hard coat layer are not impaired. In addition, the fine particles of the refractive index adjusting component may be mixed with the curable resin composition in advance, and then mixed and contained in the curable resin composition forming the hard coat layer. In addition, the fine particles of the refractive index adjusting component may be mixed with the curable resin composition in advance, and then used as is as the curable resin composition forming the hard coat layer. There are commercially available products of the fine particles of the refractive index adjusting component mixed with the curable resin composition in advance. Examples of such commercially available products include Lioduras TYZ, Lioduras TYT, and Lioduras TYM (all manufactured by Toyochem Co., Ltd.).
[0061] The curable resin composition forming the hard coat layer may contain additives such as lubricants such as silicon compounds, fluorine compounds or mixtures thereof, antioxidants, ultraviolet absorbers, antistatic agents, flame retardants such as silicone compounds, fillers, glass fibers, silica, etc. These additives may be used alone or in combination of two or more.
[0062] The thickness of the hard coat layer is not particularly limited, but is preferably 1 to 20 μm. When the thickness of the hard coat layer is 1 μm or more, sufficient hardness can be imparted to the surface of the first resin base material 1. When the thickness of the hard coat layer is 20 μm or less, the moldability and cuttability of the first resin base material 1 can be further ensured. In addition, it is also preferable in that the cure shrinkage of the hard coat layer is further suppressed, and warping and undulation of the first resin base material 1 are not caused.
[0063] When the refractive index of the first resin base material 1 is na, the refractive index nb of the hard coat layer is preferably within the range of na±0.20, more preferably within the range of na±0.15, and even more preferably within the range of na±0.10. When the refractive index nb of the hard coat layer is within the range of na±0.20, the luminance value of the light guide plate for image display 8 becomes better and color unevenness can be further prevented.
[0064] Methods for forming the hard coat layer include, for example, a method in which a coating of a curable resin composition is applied to the surface of the first resin substrate 1, and then a cured film is formed and laminated on the surface of the first resin substrate 1, but the method is not limited to this method. A known method is used as a lamination method with the first resin substrate 1. Examples of the known method include a dip coating method, a natural coating method, a reverse coating method, a comma coater method, a roll coating method, a spin coating method, a wire bar method, an extrusion method, a curtain coating method, a spray coating method, and a gravure coating method. In addition, a method of laminating a hard coat layer on the first resin substrate 1 using a transfer sheet having a hard coat layer formed on a release layer may be adopted. For the purpose of improving the adhesion between the hard coat layer and the first resin base material 1, a base film (primer layer) may be provided on the surface of the first resin base material 1 in advance.
[0065] <Method of manufacturing a light guide plate for image display> As an example of a method for manufacturing the light guide plate for image display of this embodiment, a method for manufacturing the light guide plate for image display 8 shown in FIG. 1 will be described. A first resin substrate 1 and a second resin substrate 7 are prepared ([Substrate preparation step]), and a first barrier layer 3 and a second barrier layer 5 are formed on the surfaces of the first resin substrate 1 and the second resin substrate 7 via a first anchor coat layer 2 and a second anchor coat layer 6, respectively ([Barrier layer formation step]). As a method for manufacturing the first barrier layer 3 and the second barrier layer 5, an appropriate manufacturing method is selected depending on the materials of the first barrier layer 3 and the second barrier layer 5. For example, a photosensitive material for forming a hologram is applied to the surface of the first barrier layer 3 formed on the first resin substrate 1. At this time, a transparent sealing layer having the same thickness as the hologram layer 4 may be provided on the outer periphery of the first barrier layer 3. The sealing layer seals the outer periphery of the hologram layer 4 after the hologram layer 4 is formed from the photosensitive material. The sealing layer is made of a transparent material, and for example, an epoxy resin, a silicone resin, an enethiol resin, or the like is used. Thereafter, the second resin base material 7 on which the second barrier layer 5 is formed is placed on the photosensitive material with the second barrier layer 5 facing the photosensitive material ([Light guide plate manufacturing process]). However, the above-mentioned manufacturing order is merely an example. For example, a photosensitive material may be applied to the second resin base material 7 on which the second barrier layer 5 is formed, and then the first resin base material 1 on which the first barrier layer 3 is formed may be placed on the hologram layer 4. Thereafter, the first resin substrate 1, the first anchor coat layer 2, the first barrier layer 3, the hologram layer 4, the second barrier layer 5, the second anchor coat layer 6 and the second resin substrate 7 are bonded together by a reduced pressure press to obtain a light guide plate 8 for image display. Thereafter, interference fringes corresponding to the diffraction pattern are formed on the photosensitive material, forming a diffraction grating in the photosensitive material. EXAMPLES
[0066] The present invention will be described in more detail below with reference to examples and manufacturing examples. However, the present invention is not limited to the examples and manufacturing examples described below, and various modifications are possible without departing from the gist of the present invention.
[0067] <Example 1> The material of the resin substrate is PMMA (polymethyl methacrylate, trade name "Acrylite (registered trademark), manufactured by Mitsubishi Chemical Corporation). The resin substrate is a rectangular plate with a width of 200 mm, a length of 200 mm, and a thickness of 1 mm. The material for the hard coat layer is an acrylic UV-curable resin (product name "Shikoh UV1700B", manufactured by Mitsubishi Chemical Corporation). As the material for the anchor coat layer, anchor coat solution 1 (represented as "AC-1" in Table 1, tan δ peak temperature: 78°C) in which acrylic resin 1 and isocyanate compound are mixed in a mass ratio of 10:1 is used. The barrier layer is made of silicon oxynitride.
[0068] Using the above materials, a laminate is produced by carrying out a substrate preparation step and a barrier layer formation step described below.
[0069] [Base material preparation process] In the substrate preparation step, the resin substrate is washed and dried, and then a hard coat layer is formed on the resin substrate. The resin substrate is cut into a 200 mm x 200 mm rectangle and ultrasonically cleaned for 5 minutes while immersed in a 5% aqueous surfactant solution of a neutral cleaner (product name "Semiclean (registered trademark) M-LO", manufactured by Yokohama Oil Industries Co., Ltd.). The resin substrate is then ultrasonically cleaned for 5 minutes while immersed in ultrapure water. The resin substrate is then rinsed with ultrapure water, air-dried, and then dried in a nitrogen atmosphere in an oven at 80°C. The air-dried evaluation sample is then UV-ozone cleaned for 1 minute in a UV-ozone cleaner. Next, an acrylic UV-curable resin, which is the material for the hard coat layer, is applied to both surfaces of the resin substrate using a bar coater, dried at 90°C for 1 minute, and then exposed to an integrated light dose of 500 mJ / cm 2 Both surfaces are exposed to light with a 5 μm thick hard coat layer.
[0070] [Barrier layer formation process] In the barrier layer forming step, a barrier layer is formed on the surface of the hard coat layer via an anchor coat layer. Anchor coating solution 1 is applied to the surface of the hard coating layer with a bar coater and dried at 60° C. for 1 minute to provide an anchor coating layer with a thickness of 200 nm. A silicon oxynitride film having a thickness of 100 nm is formed by reactive sputtering using silicon (manufactured by Kojundo Chemical Laboratory Co., Ltd.) as a target under the conditions shown in Table 1 while supplying oxygen gas, nitrogen gas, and argon gas. By the above operations, a laminate of Example 1 consisting of hard coat layer / resin substrate / hard coat layer / anchor coat layer (AC-1, 200 nm) / barrier layer (silicon oxynitride, 100 nm) is obtained.
[0071] Table 1 shows the resin substrate material (resin substrate material), the hard coat layer material (hard coat layer material), the anchor coat layer material (AC layer material), the deposition pressure of the barrier layer (deposition pressure [Pa]), the deposition power (power [W]), the Ar flow rate (Ar [sccm]), the O2 flow rate (O2 [sccm]), and the N2 flow rate (N2 [sccm]), as well as the barrier layer thickness (thickness [nm]) of the laminate of Example 1.
[0072] <Example 2> In Example 2, the material of the anchor coat layer is anchor coat solution 2 (referred to as "AC-2" in Table 1, tan δ peak temperature: 56°C) which is a mixture of acrylic resin 2 and isocyanate compound in a mass ratio of 10:1, and a laminate is prepared in the same manner as in Example 1, except that the thickness of the anchor coat layer, the thickness of the barrier layer, and the film formation conditions are changed as shown in Table 1. That is, the laminate of Example 2 was composed of hard coat layer / resin substrate / hard coat layer / anchor coat layer (AC-2, 100 nm) / barrier layer (silicon oxynitride, 100 nm).
[0073] Table 1 shows the resin substrate material (resin substrate material), the hard coat layer material (hard coat layer material), the anchor coat layer material (AC layer material), the deposition pressure of the barrier layer (deposition pressure [Pa]), the deposition power (power [W]), the Ar flow rate (Ar [sccm]), the O2 flow rate (O2 [sccm]), and the N2 flow rate (N2 [sccm]), as well as the barrier layer thickness (thickness [nm]) of the laminate of Example 2.
[0074] <Example 3> In Example 3, a laminate was produced in the same manner as in Example 2, except that the thickness of the anchor coat layer, the thickness of the barrier layer, and the film formation conditions were changed as shown in Table 1. That is, the laminate of Example 3 was composed of hard coat layer / resin substrate / hard coat layer / anchor coat layer (AC-2, 50 nm) / barrier layer (silicon oxynitride, 30 nm).
[0075] Table 1 shows the resin substrate material (resin substrate material), the hard coat layer material (hard coat layer material), the anchor coat layer material (AC layer material), the deposition pressure of the barrier layer (deposition pressure [Pa]), the deposition power (power [W]), the Ar flow rate (Ar [sccm]), the O2 flow rate (O2 [sccm]), and the N2 flow rate (N2 [sccm]), as well as the barrier layer thickness (thickness [nm]) of the laminate of Example 3.
[0076] <Example 4> In Example 4, the material of the anchor coat layer is anchor coat solution 3 (referred to as "AC-3" in Table 1, tan δ peak temperature: 32°C) which is a mixture of polyester resin 1 and isocyanate compound in a mass ratio of 10:1, and a laminate is prepared in the same manner as in Example 1, except that the thickness of the anchor coat layer, the thickness of the barrier layer, and the film formation conditions are changed as shown in Table 1. That is, the laminate of Example 4 was composed of hard coat layer / resin substrate / hard coat layer / anchor coat layer (AC-3, 50 nm) / barrier layer (silicon oxynitride, 40 nm).
[0077] Table 1 shows the resin substrate material (resin substrate material), the hard coat layer material (hard coat layer material), the anchor coat layer material (AC layer material), the deposition pressure of the barrier layer (deposition pressure [Pa]), the deposition power (power [W]), the Ar flow rate (Ar [sccm]), the O2 flow rate (O2 [sccm]), and the N2 flow rate (N2 [sccm]), as well as the barrier layer thickness (thickness [nm]) of the laminate of Example 4.
[0078] <Example 5> In Example 5, the material of the anchor coat layer is anchor coat solution 4 (referred to as "AC-4" in Table 1, tan δ peak temperature: 20°C) which is a mixture of polyester resin 2 and isocyanate compound in a mass ratio of 10:1, and a laminate is prepared in the same manner as in Example 1, except that the thickness of the anchor coat layer, the thickness of the barrier layer, and the film formation conditions are changed as shown in Table 1. That is, the laminate of Example 5 was composed of hard coat layer / resin substrate / hard coat layer / anchor coat layer (AC-4, 25 nm) / barrier layer (silicon oxynitride, 130 nm).
[0079] Table 1 shows the resin substrate material (resin substrate material), the hard coat layer material (hard coat layer material), the anchor coat layer material (AC layer material), the deposition pressure of the barrier layer (deposition pressure [Pa]), the deposition power (power [W]), the Ar flow rate (Ar [sccm]), the O2 flow rate (O2 [sccm]), and the N2 flow rate (N2 [sccm]), as well as the barrier layer thickness (thickness [nm]) of the laminate of Example 5.
[0080] <Comparative Example 1> In Comparative Example 1, the material of the anchor coat layer is anchor coat solution 5 (referred to as "AC-5" in Table 1, tan δ peak temperature: 72°C) which is a mixture of acrylic resin 3 and isocyanate compound in a mass ratio of 10:1, and a laminate is prepared in the same manner as in Example 1, except that the thickness of the anchor coat layer, the thickness of the barrier layer, and the film formation conditions are changed as shown in Table 1. That is, the laminate of Comparative Example 1 was composed of hard coat layer / resin substrate / hard coat layer / anchor coat layer (AC-5, 150 nm) / barrier layer (silicon oxynitride, 50 nm).
[0081] Table 1 shows the resin substrate material (resin substrate material), the hard coat layer material (hard coat layer material), the anchor coat layer material (AC layer material), the deposition pressure of the barrier layer (deposition pressure [Pa]), the deposition power (power [W]), the Ar flow rate (Ar [sccm]), the O2 flow rate (O2 [sccm]), and the N2 flow rate (N2 [sccm]), as well as the barrier layer thickness (thickness [nm]) of the laminate of Comparative Example 1.
[0082] <Comparative Example 2> In Comparative Example 2, a laminate was produced in the same manner as in Example 4, except that the thickness of the anchor coat layer, the thickness of the barrier layer, and the film formation conditions were changed as shown in Table 1. That is, the laminate of Comparative Example 2 consisted of hard coat layer / resin substrate / hard coat layer / anchor coat layer (AC-3, 100 nm) / barrier layer (silicon oxynitride, 210 nm).
[0083] Table 1 shows the resin substrate material (resin substrate material), the hard coat layer material (hard coat layer material), the anchor coat layer material (AC layer material), the deposition pressure of the barrier layer (deposition pressure [Pa]), the deposition power (power [W]), the Ar flow rate (Ar [sccm]), the O2 flow rate (O2 [sccm]), and the N2 flow rate (N2 [sccm]), as well as the barrier layer thickness (thickness [nm]) of the laminate of Comparative Example 2.
[0084] <Measurement and evaluation methods> The methods for measuring and evaluating various physical properties of the laminates obtained in the examples and comparative examples will be described below.
[0085] (tan δ peak temperature) Anchor coating solutions 1 to 5 of the examples and comparative examples were dried at 80° C. to prepare sheets having a thickness of 200 μm. The prepared sheet is subjected to viscoelasticity measurement using a dynamic viscoelasticity measuring device (DVA-200, manufactured by IT Measurement & Control Co., Ltd.) under conditions of a frequency of 1 Hz, a heating rate of 3°C / min, and a measurement temperature of -50 to 200°C, and the peak temperature [°C] of the loss tangent (tan δ) is determined.
[0086] (Elemental composition of the barrier layer) For the laminates of the examples and comparative examples, the bond energies were measured by XPS (X-ray photoelectron spectroscopy) using an X-ray photoelectron spectrometer (K-Alpha, manufactured by Thermo Fisher Scientific), and the elemental composition [atm %] was calculated by conversion from the areas of the peaks corresponding to Si2P, O1S, N1S, and C1S.
[0087] The columns "Si [atm%]," "O [atm%]," "N [atm%]," and "C [atm%]" in the "Barrier layer composition" section of Table 2 show the measured values of each element composition [atm%].
[0088] (Total light transmittance and haze) For the laminates of the examples and comparative examples, a haze meter (NDH 7000II, manufactured by Nippon Denshoku Industries Co., Ltd.) is used to measure the total light transmittance [%] and haze [%] using the JIS measurement method (total light transmittance: JIS K 7361-1, haze: JIS K 7136), with the barrier layer side of the laminate facing the light source. In addition, the laminates of the examples and comparative examples are placed in a thermo-hygrostat set at a temperature of 40°C and a relative humidity of 90% RH, and the total light transmittance [%] and haze [%] are similarly measured after 10 days.
[0089] The "Immediately after deposition" columns of "Total light transmittance [%]" and "Haze [%]" in Table 2 show the measured values of total light transmittance [%] and haze [%] immediately after deposition of the barrier layer. Additionally, the "40°C 90% 10 days" columns of "Total light transmittance [%]" and "Haze [%]" show the measured values of total light transmittance [%] and haze [%] after 10 days when the laminate was placed in a thermo-hygrostat set to conditions of 40°C and 90% RH.
[0090] (b*) For the laminates of the examples and comparative examples, a spectrophotometer (SD 6000, manufactured by Nippon Denshoku Industries Co., Ltd.) was used to measure b* under the following conditions (measurement method: transmission, specular reflection light treatment: SCI, light source: C, field of view: 2°) by placing the laminate with the barrier layer side facing the light source. Furthermore, the laminates of the examples and comparative examples are placed in a thermohygrostat set at a temperature of 40° C. and a relative humidity of 90% RH, and b* is similarly measured after 10 days.
[0091] The "b*" columns in Table 1, "Immediately after deposition" and "10 days after 40°C, 90% humidity," show the measured b* value immediately after deposition of the barrier layer and the measured b* value after 10 days when the laminate was placed in a thermo-hygrostat set to conditions of 40°C and 90% relative humidity, respectively.
[0092] (Water vapor barrier properties) Using a water vapor transmission rate measuring device (DELTAPERM, Technolox), the laminates of the examples and comparative examples were set so that the first barrier layer side was on the detector side (the first resin substrate side was on the water vapor exposure side), and the water vapor transmission rate [g / m 2 / day] is measured.
[0093] Table 2 "Water vapor transmission rate [g / m 2 The measured water vapor transmission rate is shown in the " / day" column.
[0094] [Table 1]
[0095] [Table 2]
[0096] <Explanation of results> In the laminates of Examples 1 to 5, the nitrogen element composition of the barrier layer is more than 0 atm% and 25 atm% or less, so that good optical properties are obtained in all of the total light transmittance, haze, and b*. Since these laminates have low water vapor permeability, they are also highly effective in preventing deterioration caused by the hologram layer. Furthermore, the optical properties of these laminates do not deteriorate even after storage at 40°C and 90% humidity for 10 days.
[0097] <Production Example 1> An example of manufacturing a light guide plate 8 for image display using the laminate of Example 1 will be described below. The photosensitive material for forming the hologram layer 4 is a mixture of 100 parts by mass of bisphenol-based epoxy resin jER (registered trademark) 1007 (manufactured by Mitsubishi Chemical Corporation, degree of polymerization n = 10.8, epoxy equivalent: 1750 to 2200), 50 parts by mass of triethylene glycol diacrylate, 5 parts by mass of 4,4'-bis(tert-butylphenyl)iodonium hexafluorophosphate, and 0.5 parts by mass of 3,3'-carbonylbis(7-diethylamino)coumarin, dissolved in 100 parts by mass of 2-butanone (hereinafter also referred to as "photosensitive material A").
[0098] (Light guide plate manufacturing process) In the light guide plate manufacturing process of Manufacturing Example 1, a light guide plate 8 for image display is manufactured using two sheets of the laminate of Example 1. A seal layer having a width of 5 mm and a thickness of 5 μm is applied to the peripheral portion of the barrier layer of one of the laminates. The seal layer is made of a transparent material and is not particularly limited as long as it is a material that can bond the barrier layers of the laminates to each other, but in Production Example 1, an optical adhesive (manufactured by Denka, product name "Hardlock (registered trademark) OP-1045K") is used. As a result, a seal layer stepped intermediate body is formed, the opening of which is surrounded by the seal layer and has dimensions of 50 mm x 50 mm. Thereafter, the photosensitive material A for forming the hologram layer 4 is applied onto this intermediate body by spin coating. The photosensitive material A is applied so as to have a thickness of 5 μm after drying. Thereafter, the other laminate is laminated on the hologram layer 4 via the seal layer so that the barrier layer faces the barrier layer of the intermediate body with the seal layer step, and press-laminated under reduced pressure. The press-laminated conditions are an absolute pressure of 5 kPa, a temperature of 70° C., and a press pressure of 0.04 MPa. After that, a diffraction grating is recorded in the press-bonded hologram layer 4. In this process, the temperature of the laminate including the hologram layer 4 is kept at 20°C. The diffraction grating is formed by irradiating the laminate with two laser beams and adjusting the irradiation angle and intensity of each to form interference fringes so that a required diffraction pattern is formed. In this way, the diffraction grating is recorded in the hologram layer 4. This diffraction grating is a color display diffraction grating that diffracts light in the red, green, and blue wavelength regions that is incident on the incident portion as image light, and outputs it from the display portion at positions corresponding to the pixels of the image light. Thereafter, while the laminate including the hologram layer 4 was kept at 20° C., ultraviolet light (wavelength 365 nm, irradiance 80 W / cm 2 ) was applied from one side of the laminate. 2 ) is irradiated over the entire surface for 30 seconds. A high-pressure mercury lamp is used as the source of ultraviolet light. As a result, the sealing layer is cured, and the light guide plate 8 for image display of Production Example 1 is produced. [Industrial Applicability]
[0099] The light guide plate for image display of the present invention is useful for display device applications such as VR applications and AR applications, and is useful for display device applications such as head-up displays, wearable displays, and head-mounted displays. [Explanation of symbols]
[0100] 1 First resin base material 2 First anchor coat layer 3 First Barrier Layer 4 Holographic Layer 5 Second Barrier Layer 6 Second anchor coat layer 7 Second resin base material 8 Light guide plate for image display
Claims
1. a first laminate including a first resin substrate, a first anchor coat layer, and a first barrier layer in this order; and a hologram layer, wherein silicon oxynitride accounts for 50 mass% or more of all components constituting the first barrier layer, and a nitrogen element composition in the first barrier layer determined by X-ray photoelectron spectroscopy (XPS) is more than 0 atm% and 25 atm% or less, A light guide plate for image display, wherein the material of the first anchor coat layer contains an acrylic resin, and the first anchor coat layer has a tan δ peak temperature of 56 to 80° C. in a viscoelasticity measurement.
2. 2. The light guide plate for image display according to claim 1, wherein the first resin substrate contains at least one resin selected from the group consisting of poly(meth)acrylic resins, epoxy resins, cyclic polyolefin resins, and polycarbonate resins.
3. 3. The light guide plate for image display according to claim 1, wherein the first laminate has first hard coat layers on both surfaces of the first resin substrate.
4. 4. The light guide plate for image display according to claim 1, wherein the first laminate has a total light transmittance of 90% or more.
5. 5. The light guide plate for image display according to claim 1, wherein the haze of the first laminate is less than 0.1%.
6. 6. The light guide plate for image display according to claim 1, wherein the b* of the first laminate measured by a spectrophotometer is less than 0.
5.
7. The water vapor transmission rate of the first laminate is 0.01 g / m 2 7. The light guide plate for image display according to claim 1, wherein the light guide plate for image display is less than 1000 times / day.
8. 8. The light guide plate for image display according to claim 1, wherein the nitrogen element composition in said first barrier layer is from 2 atm % to 23 atm %.
9. 9. The light guide plate for image display according to claim 1, wherein the first barrier layer has a thickness of 130 nm or less.
10. 10. The light guide plate for image display according to claim 1, wherein the first barrier layer has a thickness of 5 nm or more.
11. 11. The light guide plate for image display according to claim 1, wherein the first anchor coat layer has a thickness of 1 to 200 nm.
12. 12. The light guide plate for image display according to claim 1, wherein a total thickness of the first anchor coat layer and the first barrier layer is 300 nm or less.
13. 13. The light guide plate for image display according to claim 1, wherein a total thickness of the first anchor coat layer and the first barrier layer is 50 nm or more.
Citation Information
Patent Citations
Laminated glass with hologram layer sealed and laminated body used for production thereof
JP1995069690A
Display element including hologram and conductive layer
JP2003228052A
Gas barrier laminated material and its manufacturing method
JP2004276564A
Hologram optical recording medium
JP2008139768A
moisture barrier coating
JP2009502554A